Room temperature, single-mode 1.0 THz semiconductor source based on long-wavelength infrared quantum-cascade laser. (7th October 2020) - Hayashi, Shohei; Ito, Akio; Hitaka, Masahiro; Fujita, Kazuue
Abstract: In this work, we demonstrate a single-mode 1.0 THz quantum-cascade laser source with difference-frequency generation. The room temperature electrically pumped monolithic source is based on a long-wavelength dual-upper-state active region, in which high MIR to THz conversion efficiency is obtained. A two-section buried distributed feedback grating configuration with two different lengths is used to produce two single-mode MIR pumps, and as a result, the device exhibits single-mode THz emission with a side mode suppression ratio of ∼25 dB, at a frequency of 1.03 THz. A peak output power of 18 μ W, with a high conversion efficiency of ∼270 μ W W −2 is obtained at room temperature.